Pengaruh Profitabilitas dan Ukuran Perusahaan Terhadap Corporate Social Responsibility Pada Perusahaan Pertmbangan Yang Terdaftar Di BEI Tahun 2018-2022 - Gledira Fadia Haya; Mike Kusuma Dewi (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2024)
This research aims to test and analyze the influence of profitability and company size on corporate social responsibility in mining companies listed on the Indonesia Stock Exchange in 2018-2022. The type of research used is a quantitative method. The type of data used in this research is panel data, namely a combination of time series data and cross section data. The data source used in the research is secondary data. Of the 46 companies in the population in this study, only 13 companies met the criteria. The technique used is purposive sampling. In analyzing the data using Eviews 8 software. Based on the research results, it shows that profitability has no effect on corporate social responsibility and company size has a negative and significant effect on corporate social responsibility.